Continuous vs integral bridges - primary and secondary effects - Choudhary, Navin K.; Duggal, S.K.; Mehta, P.K.; Gopal, Sheo (Journal of Structural Engineering, 2024)
The Continuous and Integral bridges are constructed to economically span longer distances and are suitable for certain foundation types. The movement joints and bearings in continuous bridges can cause severe maintenance issues during the service life of the structure. To overcome these problems and to span further long distances, the Integral bridges also known as Rigid Frame bridges are adopted. The Integral bridges are structures with no movement joints or bearings. The Semi-Integral bridges are integral at piers and articulated by bearings at the abutments. The durability of such bridges is greatly improved by removing or minimising the movement joints and bearings. For spanning further longer distances, the pre-stressed concrete construction is used. Due to the supporting system and the method of construction, the secondary stresses are developed which may sometimes be comparable to the primary effects due to Dead, Live and Impact loads. The parameters influencing the design are cross section of deck, additional stiffening elements, span to depth ratio, the support type, and loading arrangements. The abutments and piers are made composite with the deck and hence move horizontally in response to temperature fluctuations. This paper presents a comparison of the primary and secondary forces developed in Continuous and Integral bridges.